An Epitope‐Imprinted Biointerface with Dynamic Bioactivity for Modulating Cell–Biomaterial Interactions. (16th October 2017) - Pan, Guoqing; Shinde, Sudhirkumar; Yeung, Sing Yee; Jakštaitė, Miglė; Li, Qianjin; Wingren, Anette Gjörloff; Sellergren, Börje
Abstract: In this study, an epitope‐imprinting strategy was employed for the dynamic display of bioactive ligands on a material interface. An imprinted surface was initially designed to exhibit specific affinity towards a short peptide (i.e., the epitope). This surface was subsequently used to anchor an epitope‐tagged cell‐adhesive peptide ligand (RGD: Arg‐Gly‐Asp). Owing to reversible epitope‐binding affinity, ligand presentation and thereby cell adhesion could be controlled. As compared to current strategies for the fabrication of dynamic biointerfaces, for example, through reversible covalent or host–guest interactions, such a molecularly tunable dynamic system based on a surface‐imprinting process may unlock new applications in in situ cell biology, diagnostics, and regenerative medicine.